Gestão escolar e educação especial: um programa de web rádio como intervenção pedagógica em escola de educação básica de Santa Maria - Silva, Camila Rodrigues da (2024)
This research is linked to the Postgraduate Program in Public Policies and Educational Management, at the Federal University of Santa Maria (UFSM). It belongs to the research line LP2 - Pedagogical Management and Educational Contexts and is linked to the actions of the research group Teaching, School and Teacher Training (DOCEFORM). The general objective is to build a web radio program based on the understanding of Educational Policies and the impacts on the forms of management of Special Education practices in Basic Education Schools in Santa Maria. Based on this, the research problem that presents itself is: what elements are taken into consideration in the construction of a web radio program, transversalizing the interpretations of Educational Policies and the management of Special Education work in a regular school? The methodology has a qualitative approach and the instruments used for data collection were narrative interviews. They were organized with the purpose of answering the following questions: how is the organization of Special Education management characterized in a Basic Education school in the municipality of Santa Maria? What difficulties are perceived for the implementation of Special Education Policies? And also, what contributions could a web radio program bring to the organization of Special Education management? The research context was a state school, located in the city of Santa Maria, Camobi neighborhood. The authors brought into dialogue are Management scholars such as Paro (2002, 2008, 2013), Libâneo (2007), among others, and Special Education scholars such as Mantoan (2003) and Carvalho (2005), together with the regulations of the main Public Policies aimed at people with disabilities. As categories of analysis we have the role of the interviewee in the organization and development of inclusive processes, the spaces for organizing and discussing inclusive practices, the involvement of teaching staff in inclusive processes, the implementation of Special Education policies and their difficulties, changes to qualify Special Education at school and the web radio program as a pedagogical intervention, which is the product of the research, titled Hablaae, with five episodes involving Special Education themes, according to a collective construction process, in which the voices of family members are considered, in a respectful and constructive way, favoring joint reflection on the subthemes developed.